Macroprudential Banking Supervision & Monetary Policy Legal Interaction in the European Union - Amorello, Luca (Springer International Publishing, 2018)
The European experience suggests that the efforts made to achieve an efficient trade-off between monetary policy and prudential supervision ultimately failed. The severity of the global crisis have pushed central banks to explore innovative tools-within or beyond their statutory constraints-capable of restoring the smooth functioning of the financial cycle, including setting macroprudential policy instruments in the regulatory toolkit. But macroprudential and monetary policies, by sharing multiple transmission channels, may interact-and conflict-with each other. Such conflicts may represent not only an economic challenge in the pursuit of price and financial stability, but also a legal uncertainty characterizing the regulatory developments of the EU macroprudential and monetary frameworks. In analyzing the "legal interaction" between the two frameworks in the EU, this book seeks to provide evidence of the inconsistencies associated with the structural separation of macroprudential and monetary frameworks, shedding light upon the legal instruments that could reconcile any potential policy inconsistency.